Pengaruh Latihan Sirkuit terhadap Peningkatan Tendangan Sabit Atlet Pencak Silat Kabupaten Balangan: Systematic Literature Review - Juliansyah, Ahmad; Mashud (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study aims to systematically analyze and synthesize various research findings regarding the effectiveness of circuit training models on improving sickle kick skills in pencak silat. The approach used was a Systematic Literature Review (SLR), with data sources from Google Scholar and Crossref for the period 2019–2024. Article selection was carried out using the PRISMA method, and analysis was carried out using the PICO approach. The results of the review of 8 research articles showed that circuit training consistently improved leg muscle strength, agility, and accuracy of sickle kick techniques. The implications of these findings support the integration of circuit training into the physical training program of pencak silat athletes at the regional level, including Balangan Regency.